A polêmica como modalidade argumentativa: a manifestação no discurso midiático - Carbonera, Renata Getelina (2019)
This research aims to verify how the controversies are built in media statements. The main objective of this study is to analyze media statements, investigating constitutive characteristics that can make them controversial, in order to understand the effects of meaning produced. Such research is justified by the fact that the term controversy has gained a great importance in social interactions today, and often is misused. The theoretical approach is based on Mikhail Bakhtin (1997, 2003, 2008, 2010, 2014, 2016), the text theorist who contributes to the understanding of the concepts of discourse genres, enunciation, dialogue and dialogism; Ruth Amossy (2017), to understand the concept of controversy and understand how it manifests itself in the clippings of the discourses under analysis. Regarding the methodology, this study has a descriptive, analytical and bibliographic nature with a qualitative approach. The corpus of research of this work are clippings of four media utterances, which gained great public repercussion for their controversial character, especially in social networks, in 2019. The analysis revealed that the chosen utterances have characteristics that make them controversial. and that the controversy goes far beyond an attributed characteristic and this or that utterance, but it can be considered an argumentative modality that permeates various discursive genres.